Back pain in a previously healthy teenager. (17th July 2013) - Fitzgerald, Felicity; Howard, Julia; Bailey, Fiona; Soleimanian, Sorrush
Abstract : We present the case of a 14-year-old previously healthy boy who presented to his general practitioner with back pain and fever after rugby training. He was initially treated for suspected discitis but during the course of his admission he rapidly deteriorated and developed severe necrotising pneumonia. He was intubated, ventilated and transferred to a paediatric intensive care unit. Panton-Valentine leukocidin Staphylococcus aureus was suspected and subsequently identified in blood cultures.